Non-Formal Physical Education of Children: Increase Factor of Physical Activity and Physical Fitness (Baltic Journal of Sport and Health Sciences, 2016)
Background.  Studies  on  physical  activity,  which  is  positively  associated  with  physical  fitness,  reveal  that children’s  activity  is  not  sufficient  (BHFNC,  2010;  Chen,  Zheng,  Yi,  &  Yao,  2014;  Currie  et  al.,  2012),  and their  physical  fitness  deteriorates  (Volbekienė  &  Kavaliauskas,  2002;  Мирошниченко  &  Астраханцев,  2005; Синявский, Власов, & Сергеев, 2009). Non-formal physical education (NFPE) is one of the means to increase children’s physical activity and physical fitness. The aim of this study was to determine the influence of NFPE on the physical fitness of 6th grade pupils. Methods. The research was conducted in May, 2013; 356 six-graders (48.0% of girls) from four Klaipėda city comprehensive schools participated in the research. As many as 56.5% of children (48.3% of girls) participated in NFPE in school and out of school. The participants completed five physical fitness tests. Results. Independent t test revealed that the results of boys who attended the NFPE group of cardiorespiratory fitness, t(180) = −2.093, p = .038; upper body muscular strength and endurance, t(182) = 2.413, p = .017; abdominal muscular strength and endurance, t(186) = 3.282, p = .001; explosive leg power, t(183) = 1.967, p = .049, and girls’ results of abdominal muscular strength and endurance, t(172) = 2.687, p = .008 were significantly higher than those in the NFPE non attended group.Conclusion.  Non-formal  physical  education  is  a  meaningful  educational  form  for  increasing  children’s, particularly boys’, health related physical fitness; therefore it is purposeful to encourage children to participate in physical activities in school and after classes.Keywords:  non-formal physical education, physical fitness, testing.